Being for the Other: Surveillance and Depictions of Race, Gender, and Animals in Contemporary South African Fiction - Laue, Kharys Ateh (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2016)
This thesis examines the depiction, in contemporary South African fiction, of irresponsibility and responsibility in relation to the raced, gendered, and animal Other. Through a close analysis of Jeremy Bentham's Panopticon prison and Michel Foucault's study of this design, I establish the notion of disciplinary surveillance or panopticism. This I take to be a mode of power that seeks, by means of an invisible gaze, to render its subjects docile. In my readings of J. M. Coetzee's Waiting for the Barbarians, Zoë Wicomb's Playing in the Light, Justin Cartwright's White Lightning, and selected short stories from Wicomb's You Can't Get Lost in Cape Town and The One That Got Away, I demonstrate that oppressive authoritarian regimes are rooted in Benthamic principles of hyper-visibility and concealment. Disciplinary power, I contend, is effective precisely because it places an individual in a constant state of Being-for-Others, a term coined by Jean-Paul Sartre to describe the experience of objectification through another's look. Judith Butler's concept of gender performativity and W. E. B. Du Bois's notion of black double consciousness frame my examination of, respectively, gender and racial oppression, while my discussion of animals appeals to Jacques Derrida's work on the non-human. I show how surveillance, in each of the selected texts, functions through a racist and/or sexist and/or speciesist gaze that facilitates violent, irresponsible relationships with the human and non-human Other. The texts under discussion, however, also depict ways in which the Other actively resists and subverts regimes of oppression, often by means of a counter gaze that compels the protagonist, or the reader, to take up responsibility for Others. Ultimately, my study concludes that the fictional works of Coetzee, Wicomb, and Cartwright offer an ethics of empathetic responsibility, which I term Being for the Other, in opposition to mechanisms of disciplinary surveillance that seek to oppress, conceal, and dominate.
Keywords: Uncatalogued